Poultry thermoregulation in the heat : seasonal acclimatization and partitioning of evaporative water losses - Nkukwana, Thobela T. (University of Pretoria, 2023)
Dissertation (MSc (Animal Science: Animal Physiology))--University of Pretoria, 2023.